Perception of schizophrenic’s relatives about the disease - Janmille Morais Xavier; Eliane Magalhães de Brito; Rita Neuma Dantas Cavalcante de Abreu; Thereza Maria Magalhães Moreira; Lucilane Maria Sales da Silva; Silvânia Maria Mendes Vasconcelos (Revista Brasileira em Promoção da Saúde, 2012)
Objective: To understand the perception of schizophrenic’s relatives about the disease. Methods: This is a descriptive, qualitative study performed with ten family members of people with medical diagnosis of schizophrenia treated by the Center for Psychosocial Care (CAPS) in a municipality of Ceará. Unstructured interview was used as a strategy to collect data. Data analysis was based on the method of content analysis proposed by Bardin (1997). Results: The identified categories were: identification of disease; treatment of schizophrenia; difficulties experienced by relatives; search for quality of life by people with schizophrenia. Conclusion: In the speech of schizophrenic’s relatives, gaps are perceived in knowledge concerning the diagnosis of the disease, which point at the importance of this aspect being clarified during the meetings between professionals, users and family members. However, other aspects of the disease, such as behavioral disorders and types of treatments, were mentioned by the study participants.